Transforming knowledge to wisdom: Feng Qi and the new Neo-Marxist humanism - Rošker, Jana S. (Asian philosophy, 2023)
This paper introduces the philosophical theory of Feng Qi, an important modern Chinese philosopher, who is practically unknown in the West. I argue that his theory of knowledge is not limited to epistemology in the strict and narrow sense, but also refers to ontological and metaphysical issues. The paper shows how Feng Qi integrated ontological and ethical suppositions into the framework of what he called ‘expanded epistemology’. In this way, he offers an innovative solution to several problems, linked to the dichotomous relations of substance and phenomena. The article analyses and interprets his theoretical system in order to highlight that it represents an important contribution to comparative epistemology and its underlying methodology.